Pengembangan Skor Risiko KARIADI Sebagai Metode Stratifikasi Risiko Kejadian Kardiovaskular Mayor Pasca Intervensi Koroner Perkutan Primer - Asrial, An Aldia; Herry, Yan; Udin, Bahrudin; Anggriyani, Novi; Suhartono, Suhartono (RSUP Dr. Kariadi, 2022)
Background Reduction of major cardiovascular events (MACE) in ST elevation acute coronary syndrome (STE-ACS) patients has been achieved by primary percutaneous coronary intervention (PCI) strategy and intensive care management. However, the intensive care unit bed availability and cost remain a problem for those patients, and thus risk stratification using an objective risk score instrument is required. Aim To develop a risk score of in-hospital MACE for patients with STE-ACS underwent primary PCI. Methods A cohort study of 208 patients with STE-ACS undergoing primary PCI at the Dr. Kariadi General Hospital Semarang. Predictor analysis was carried out using bivariate Chi-Square test and multivariate logistic regression. The obtained independent predictors were then used as risk score variables. The quality of the risk score was tested by the Hosmer and Lemeshow calibration test and AUC ROC analysis for discrimination test. Results Seven out of 13 independent predictors, i.e. Killip class (OR 20,04, p=0,0001), age (OR 3,02, p=0,04), renal insufficiency (OR 9,48, p=0,007), infark related artery final TIMI flow (OR 11,57, p=0,001), admission systolic blood pressure (OR 3,04, p=0,025), duration of total ischaemic time (OR 3,14,p=0,032) and increase of blood glucose levels (OR 3,04, p=0,029) were fulfilled the criteria for risk scores of in-hospital MACE. The risk scores had a good quality with the Hosmer and Lemeshow calibration test> 0,05 and ROC AUC 0,886 (95% CI, 0,827-0,944, p <0,005). Conclusions A risk scoring modele consisting of 7 independent predictor variables i.e. Killip class, age, renal insufficiency, infark related artery final TIMI flow, admission systolic blood pressure, duration of total ischaemic time, and increase of blood glucose levels (KARIADI) has a good calibration and discrimination in predicting the risk of in-hospital MACE in patients with STE-ACS underwent primary PCI. Keywords Predictors of in-hospital MACE, primary PCI, ST-segment elevation acute coronary syndromes, risk score.